A quantitative comparison of apically extruded debris during root canal preparation using NiTi full-sequence rotary and single-file rotary systems: An in vitro study - Pallavi Goel; R. Vikram; R. Anithakumari; M. S. Adarsha; M. E. Sudhanva (Wolters Kluwer Medknow Publications, 2024)
Aim: The purpose of this study was to compare quantitatively the apically extruded debris during root canal preparation using NiTi full-sequence rotary and single-file rotary systems. Methods: Sixty extracted mandibular premolar teeth with single canals and similar lengths were used and divided into four groups. Groups A and B are NiTi full-sequence rotary systems and Groups C and D are single-file rotary systems. In Group A, the canals were prepared using V-Taper 2H file (up to 25/0.06), Group B: TruNatomy file (up to 26/0.04), Group C: OneShape file (25/0.06), and Group D: OneCurve file (25/0.04). The initial weight of each Eppendorf tube to be used was calculated using an analytical balance before instrumentation. After instrumentation, the tubes were then stored for 15 days in an incubator at 37°C. The Eppendorf tubes were weighed again to determine their final weight which contained the extruded debris. The data were statistically analyzed using a one-way ANOVA test and Tukey's post hoc test. Results: The OneCurve single-file system resulted in statistically significant less debris extrusion than the OneShape single-file system, TruNatomy multifile system, and V-Taper 2H multifile system (P < 0.001). Among the full-sequence rotary file systems, the TruNatomy rotary file system produced statistically significantly less debris extrusion than the V-Taper 2H rotary file system (P = 0.01). Conclusion: All the instrumentation systems caused apical extrusion of debris. OneCurve system showed least debris extrusion, followed by OneShape, TruNatomy, and V-Taper 2H systems. Thus, single-file rotary instruments performed better with the less extrusion of debris when compared to multifile rotary systems.